ABIOTIC FACTORS INFLUENCING MANTANGAN (Merremia peltata) INVASION IN BUKIT BARISAN SELATAN NATIONAL PARK - Master, Jani; Tjitrosoedirdjo, Soekisman; Qayim, Ibnul (BIOTROPIA, 2016)
Some areas in Bukit Barisan Selatan National Park have serious problems related to Merremia peltata (Family Convolvulaceae) invasion. The abiotic factors influencing M. peltata invasion were investigated in this study. This research compared abiotic factors in three forest locations with different invasion levels i.e.severe, moderate and mild invasions. Abiotic factors measured were percentage of tree canopy coverage, micro climate factors (temperature and humidity), elevation above sea level and physical and chemical properties of the soil surface. In this study, canopy coverage is classified as abiotic factors because it influencesthe intensity of light that can reach the forestfloor. Aposthoc Duncan's Multiple Range Test (DMRT) was employed to determine significant differences (p<0.05) among abiotic factors. In addition, a test of correlation and multiple linear regression were conducted to determine the relationships between abiotic factors and M. peltata invasion. Multiple regression testing showed that canopy coverage significantly (p<0.05) influenced M. peltata invasion. Based on the generated model, a 1% addition of canopy coverage would decrease M. peltata invasion by 2.8%. Multiple linear regression analysis was used to predict the relationship between soil nutrients and invasion. The C/N ratio and P2O5, Ca, Mg and Na concentration significantly (p<0.05) influenced invasion level. Again, based on the generated model, the increase in the C/N ratio aswell as in P2O5 and Ca concentrations were correlated with the reduction of M. peltata invasion; while the increase of Mg and Na concentrations were correlated with the increase of M. peltata invasion. M. peltata invasion in Bukit Barisan Selatan National Park was influenced by opened forest canopy andwas correlated with high concentration of Na and Mg in the soil of the invaded forest areas. Keywords: Bukit Barisan Selatan National Park, invasive species, mantangan, Merremia peltata